Work Experience, Accounting Expertise, and Organizational Culture as Economic Factors in Improving Financial Statement Quality in Jayapura Cooperatives - Wambon, Thomas Sergius; Salle, Agustinus; Matani, Cornelia Desiana (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to examine the effect of work experience, accounting understanding and organizational culture on the quality of financial reports in cooperatives in Jayapura city. This questionnaire was distributed to 60 respondents in 26 cooperatives consisting of cooperative leaders, staff involved in the preparation of financial reports and cooperatives that have published financial reports. The sampling technique used purposive sampling. Data processing in this study used the WarpPLS 8.0 software application. The results of the study showed that work experience did not show a significant effect on the quality of financial reports in cooperatives while accounting understanding and organizational culture had a significant effect on the quality of financial reports in cooperatives in this study.